(3GdLjhHhdjJjc hGdGSJQGJjLjGJ GdCefjI (B=s Geopolitics and security strategies : "(3GdCef ef efXhQ LZQGaj(B" /s - (3YHO GdeWdH, eeOhM YHO GdMejO,s 1955- ((3GdTGQbI, GdEeGQGJ GdYQHjI GdeJMOI (B:s (3TQWI GdTGQbI, eQcR HMhK GdTQWI,s, 2001)
(3jJfGhd cJGH (B((3GdLjhHhdjJjc hGdGSJQGJjLjGJ GdCefjI (B: "(3GdCef ef efXhQ LZQGaj(B") (3hGdPj bGe HJCdjag (B((3eeOhM YHO GdMejO YHO GdeWdH(B) (3aj MhGdj (B(42) (3UaMI ef GdbWY GdeJhSW ehGVjY (B((3GdLZQGajG GdSjGSjI hGdCef(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdaUd GdChd (B: (3GdLZQGajG GdSjGSjI hJCKjQGJgG GdCefjI GdeHMK GdChd (B: (3fTCI hJWhQ OQGSI GdLZQGajG GdSjGSjI hYdGbGJgG, GdeHMK GdKGfj (B: (3YdGbGJ GdScGf OGNd GdOhdI hJhRjY GdYdGbGJ GdCefjI, GdeHMK GdKGdK (B: (3GdfeW GdLZQGajG ddOhd hJCKjQg GdCefj, GdeHMK GdQGHY (B: (3GdMOhO GdSjGSjI Hjf GdOhd hGfYcGSGJgG GdCefjI, GdeHMK GdNGeS (B: (3GdLZQGajG GdCefjI ; GdaUd GdKGfj (B: (3GdLZQGajG GdScGfjI heOdhdGJgG GdCefjI, GdeHMK GdChd (B: (3eaGgje GdOQGSGJ GdScGfjI GdCefjI, GdeHMK GdKGfj (B: (3feh GdScGf hJhRjYge hcKGaGJge hCKQ Pdc Ydi GdCef, GdeHMK GdKGdK (B: (3GdScGf hGdeTGcd GdGbJUGOjI hGdGLJeGYjI hGdCefjI(B. s
(3eSJNdU (B: (3UaMI (B4.s
(3HHdjhLQGajI (B: (3UaMI (B41-42.s
Keywords: (3GdLZQGajG GdSjGSjIs; (3GdCef GdOGNdjs